Tudo que precisei criar para me manter viva – transinvenção, pesquisa drag e performance não-binária no fim do mundo (deles) - Muniz, Levi Banida Mota (2021)
I warn you with affection: in this work I speak very intimately for those who will read it, as I speak in it how I have organized initiatives, being a monster and non-binary body, to maintain my life. In this sharing, I propose an (anti)methodology of performance creation through four counter-devices, Programa-Linha-Teia-Emaranhado. These act as elements to think the dialogues between performative actions in an in performance. For this, I present possibilities of encounter-friction between more than thirty performances made from 2017 to 2021. The initiatives dialogue about transgender, undisciplined methodologies of creation, maintenance of dissident existences amidst the political, social, climatic and environmental chaos. I create a text-performative universe that collides verbs, QR Codes, images, among other materialities, divided into five notebooks that can be read autonomously or concatenated. Reading-writing is an invitation: that we all devise our undisciplined, insubordinate and disobedient strategies of preservation and invention.